Magnetoresistance in high oxidation state iron oxides - Battle, P; Green, M; Lago, J; Mihut, A; Rosseinsky, M; Spring, L; Singleton, J; Vente, J (1998)
Magnetoresistance is observed in non-ferromagnetic oxides containing FeIV which have magnetic behaviour characteristic of small magnetic clusters.